Pemberdayaan Ekonomi Masyarakat Tani Lahana Kering Melalui Pengembangan Usahatani Terpadu Berbasis Ternak Sapi Bali di Desa Selengan Kecamatan Kayangan Kabupaten Lombok Utara - M. Yusuf; Muji Rahayu; Muhammad Nursan; Aeko Fria Utama FR; Dudi Septiadi; Pande Komang Suparyana (Universitas Mataram, 2022)
In general, this community service activity aims to increase the knowledge and skills of the dry land farming community through the development of an integrated farming system based on Bali cattle in Selengan Village, Kayangan District, North Lombok District, while the specific objectives are: (1) Fostering interest and motivating the people of Selengan Village, Subdistrict Kayangan, North Lombok District for entrepreneurship in agriculture and animal husbandry, especially Bali cattle breeding; (2) Showing farmers about aspects of integrated farming technology based on Bali cattle; (3) Farmers can recognize the socio-economic aspects (sustainable increase in income) of an integrated farming system based on Bali cattle; and (4) Establishing relationships between universities, especially Mataram University with the community. Implementation is carried out using community development methods that emphasize adult learning (andragogy), involving 10 members of the target farmer group and carried out through counseling, demonstrations, and demonstration plots. The results of the implementation show that: (1) This community service activity has been able to increase the knowledge and skills of participants, especially those related to: (a) technical aspects and socio-economic aspects, especially related to improving the economy of land farming communities by developing an integrated farming system based on cattle. Bali; (b) Good, healthy, and environmentally friendly agricultural management; and (c) the ability of group management in an effort to take advantage of the existing potential; (2) The response of members of farmer groups to extension activities and economic empowerment of dry land farming communities is quite high; (3) The percentage rate of growth of fodder crops (turi and elephant grass) is quite high + 89%; (4) The average income of farmers from the development of cattle-based integrated farming is Rp. 4,270.00/person/year; and (5) This activity has also contributed to the intensification of reciprocal communication between the local government of North Lombok District universities, UNRAM and farming communities who are members of dryland farmer groups in Selengan Village, Kayangan District, North Lombok District.